A Research on the Awareness Levels of Secondary School Students about Some Concepts Related to Agriculture: An Example of Kars - E. Berna Gücüm; Yasin Çalışır (e-Kafkas Eğitim Araştırmaları Dergisi)
This study aims to determine the awareness levels of our students residing in urban and rural areas regarding their perceptions of selected current fundamental concepts which are related to interdisciplinary learning-based agriculture. The data are collected with a questionnaire containing 16 current agricultural concepts developed by the researcher. Survey research, which is one of the quantitative research methods, is used as the research method. The study is conducted with 1209 secondary school students (5-8th grades) using a layered purposive sampling method. The results show that the awareness levels of the students participating in this study regarding current concepts in agriculture differ in gender, class level, father's profession, and the characteristics of the place of residence. Despite variations in some concepts, in general, it is observed that male students in 7th and 8th grades, the students whose fathers are farmers, and those residing in villages and county towns have an advantage in terms of the gender variable. It is observed that our students have lower knowledge levels in terms of heirloom, genetically modified seeds, medicinal and aromatic plants, and agricultural ecology among the 16 current concepts and they seem to be more knowledgeable about concepts such as good farming practices, desertification, water management, drought, human-induced soil degradation, food safety, and conservation of plant. Especially our students, who are the future of our society, need to have basic knowledge about agriculture in order to make decisions about agriculture. In the light of the results obtained from our study, it can be said that teaching agriculture as a course in secondary schools or including these subjects in the content of science courses will contribute to our country and our world.